The Influence of Lean Healthcare and Service Excellence on Operational Efficiency and Patient Loyalty at GlucoCare Pharmacy - W. Isro Abdilah; Aris Ismail; Emiliana Sri Pudjiarti (Proceeding of The International Conference on Business and Economics, 2026)
This study aims to analyze the influence of Lean Healthcare and Service Excellence on patient loyalty with operational efficiency as a mediating variable in a specialized metabolic pharmacy network. A quantitative study with an explanatory design was conducted on patients at 11 branches of GlucoCare Pharmacy using proportionate stratified random sampling. Data were collected through structured questionnaires with a Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results showed that Lean Healthcare and Service Excellence had a positive and significant effect on operational efficiency, with Service Excellence as the strongest predictor. Both also had a direct positive and significant effect on patient loyalty. Furthermore, operational efficiency was proven to have a significant effect on patient loyalty and served as a partial mediator (complementary mediation) in the relationship between Lean Healthcare and Service Excellence on patient loyalty. The research model demonstrated strong explanatory power for the variation in operational efficiency and patient loyalty.